Zika Virus Envelope Domain III Recombinant Protein Delivered With Saponin-Based Nanoadjuvant From Quillaja brasiliensis Enhances Anti-Zika Immune Responses, Including Neutralizing Antibodies and Splenocyte Proliferation - Cibulski, Samuel; Varela, Ana Paula Muterle; Teixeira, Thais Fumaco; Cancela, Martín Pablo; Sesterheim, Patrícia; Souza, Diogo Onofre; Roehe, Paulo Michel; Silveira, Fernando (Frontiers in Immunology, 2021)
Nanoadjuvants that combine immunostimulatory properties and delivery systems reportedly bestow major improvements on the efficacy of recombinant, protein-based vaccines. Among these, self-assembled micellar formulations named ISCOMs (immune stimulating complexes) show a great ability to trigger powerful immunological responses against infectious pathogens. Here, a nanoadjuvant preparation, based on saponins from Quillaja brasiliensis, was evaluated together with an experimental Zika virus (ZIKV) vaccine (IQB80-zEDIII) and compared to an equivalent vaccine with alum as the standard adjuvant. The preparations were administered to mice in two doses (on days zero and 14) and immune responses were evaluated on day 28 post-priming. Serum levels of anti-Zika virus IgG, IgG1, IgG2b, IgG2c, IgG3 were significantly increased by the nanoadjuvant vaccine, compared to the mice that received the alum-adjuvanted vaccine or the unadjuvanted vaccine. In addition, a robust production of neutralizing antibodies and in vitro splenocyte proliferative responses were observed in mice immunized with IQB80-zEDIII nanoformulated vaccine. Therefore, the IQB80-zEDIII recombinant preparation seems to be a suitable candidate vaccine for ZIKV. Overall, this study identified saponin-based delivery systems as an adequate adjuvant for recombinant ZIKV vaccines and has important implications for recombinant protein-based vaccine formulations against other flaviviruses and possibly enveloped viruses.